The Energetic Potential for Undiscovered Manganese Metabolisms in Nature - LaRowe, Douglas E.; Carlson, Harold K.; Amend, Jan P. (Frontiers in Microbiology, 2021)
Microorganisms are found in nearly every surface and near-surface environment, where they gain energy by catalyzing reactions among a wide variety of chemical compounds. The discovery of new catabolic strategies and microbial habitats can therefore be guided by determining which redox reactions can supply energy under environmentally-relevant conditions. In this study, we have explored the thermodynamic potential of redox reactions involving manganese, one of the most abundant transition metals in the Earth’s crust. In particular, we have assessed the Gibbs energies of comproportionation and disproportionation reactions involving Mn2+ and several Mn-bearing oxide and oxyhydroxide minerals containing Mn in the +II, +III and +IV oxidation states as a function of temperature (0 – 100oC) and pH (1 – 13). In addition, we also calculated the energetic potential of Mn2+ oxidation coupled to O2, NO2-, NO3- and FeOOH. Results show that these reactions — none of which, except O2 + Mn2+, are known catabolisms —can provide energy to microorganisms, particularly at higher pH values and temperatures. Comproportionation between Mn2+ and pyrolusite, for example, can yield 10s of kJ (mol Mn)-1. Disproportionation of Mn3+ can yield more than 100 kJ (mol Mn)-1 at conditions relevant to natural settings such as sediments, ferromanganese nodules and crusts, bioreactors and suboxic portions of the water column. Of the Mn2+ oxidation reactions, the one with nitrite as the electron acceptor is most energy yielding under most combinations of pH and temperature. We posit that several Mn redox reactions represent heretofore unknown microbial metabolisms.